2017
DOI: 10.1159/000486973
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Effects of Intravenous Diacetylmorphine on the Methylation of <b><i>POMC</i></b> and <b><i>NR3C1</i></b>

Abstract: The administration of diacetylmorphine (DAM) reduces the activation of the hypothalamic-pituitary-adrenal (HPA) axis in opioid-maintained patients. However, the epigenetic effects of DAM on addiction-related genes have not been investigated yet. In a randomized controlled study, we examined the immediate effects of intravenous DAM versus placebo on the promoter methylation of the POMC (pro- opiomelanocortin) and NR3C1 (glucocorticoid receptor 1) genes. Twenty-eight heroin-dependent patients on DAM-assisted tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…Interestingly, acute methylation changes after the last ECT differed between patients: ECT-R showed a decrease, and ECT-NR an increase in POMC promoter methylation. Rapid changes in POMC m have also been observed in other studies, e. g., an increase in POMC promoter methylation 10 min after injection of diacetylmorphine in opioid-dependent patients 24 . The decreasing POMC m after the last ECT in ECT-R might reflect a normalized HPA axis.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Interestingly, acute methylation changes after the last ECT differed between patients: ECT-R showed a decrease, and ECT-NR an increase in POMC promoter methylation. Rapid changes in POMC m have also been observed in other studies, e. g., an increase in POMC promoter methylation 10 min after injection of diacetylmorphine in opioid-dependent patients 24 . The decreasing POMC m after the last ECT in ECT-R might reflect a normalized HPA axis.…”
Section: Discussionsupporting
confidence: 69%
“…Altered HPA axis hormones such as corticotropin-releasing hormone, adrenocorticotropic hormone (ACTH), and cortisol are indicators pointing towards lowered stress resilience in depressed individuals 15 16 17 18 19 . Transcription of the gene coding for proopiomelanocortin (POMC) – a pituitary prohormone of ACTH – plays a role in various somatic (e. g., tumors 20 , metabolic syndrome 21 ) as well as mental illnesses (e. g., alcohol dependence 22 23 , heroin addiction 24 , or eating disorders 25 ). In rodents, early life stress led to HPA axis hyperactivity and depression-like behavior associated with persistent hypomethylation in the distal promoter region of Pomc 26 .…”
Section: Introductionmentioning
confidence: 99%
“…24 Studies have pointed out that heroin addicts treated with intravenous diacetylmorphine could cause an POMC promoter methylation and reduce the level of stress hormone in the patient's body, thus playing a role in emotional regulation of treatment. 25 In alcohol dependence, POMC promoter methylation is associated with craving. 26 The degree of POMC promoter methylation in smokers is significantly higher than that in nonsmokers.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that epigenetics, especially DNA methylation, play an important role in the occurrence, development, and progression of psychiatric disorders. In addition, research on epigenetics proves that environmental factors are also closely related to the occurrence of diseases [62,63]. Nonetheless, literature on these genes is extremely poor, and, therefore, further research is required to confirm or reject the hypothesis of their non-association with SB.…”
Section: Main Findingsmentioning
confidence: 99%